2016
DOI: 10.1111/ced.12991
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic spinal cord compression from basal cell carcinoma of the skin treated with surgical decompression and vismodegib: case report and review of Hedgehog signalling pathway inhibition in advanced basal cell carcinoma

Abstract: We report a case of a 66-year-old man with locally advanced and metastatic basal cell carcinoma (BCC) causing spinal cord compression, which was treated with spinal surgery and subsequent vismodegib. The patient presented with a large fungating chest wall lesion and a metastasis in T8 that was causing cord compression. He had neurosurgical decompression of the T8 lesion and fixation of the spine. Punch biopsy from the fungating chest wall lesion showed a BCC with some malignant squamous differentiation (basosq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 9 publications
(29 reference statements)
0
10
0
Order By: Relevance
“…On the other hand, the largest published cohort study with 1675 patients suggested that vismodegib is not associated with an increased risk of SCC while a systematic and a narrative review of the literature concluded that the existing evidence does not justify an association between vismodegib and SCC formation [ 31 , 51 , 52 ]. Moreover, there are three very recent case reports including four patients in total which provide preliminary evidence that vismodegib might be effective for difficult-to-treat BSC ( Table 2 ) [ 53 , 54 , 55 ]. In all of them, the lesions did not “transform” into purely squamous tumors but in contrast they completely remitted and in two cases the remission was maintained for a very long period of time [ 53 , 54 , 55 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the largest published cohort study with 1675 patients suggested that vismodegib is not associated with an increased risk of SCC while a systematic and a narrative review of the literature concluded that the existing evidence does not justify an association between vismodegib and SCC formation [ 31 , 51 , 52 ]. Moreover, there are three very recent case reports including four patients in total which provide preliminary evidence that vismodegib might be effective for difficult-to-treat BSC ( Table 2 ) [ 53 , 54 , 55 ]. In all of them, the lesions did not “transform” into purely squamous tumors but in contrast they completely remitted and in two cases the remission was maintained for a very long period of time [ 53 , 54 , 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, there are three very recent case reports including four patients in total which provide preliminary evidence that vismodegib might be effective for difficult-to-treat BSC ( Table 2 ) [ 53 , 54 , 55 ]. In all of them, the lesions did not “transform” into purely squamous tumors but in contrast they completely remitted and in two cases the remission was maintained for a very long period of time [ 53 , 54 , 55 ]. Although the effect of vismodegib on BSC treatment definitely requires further investigation in larger controlled studies, it could prove to be a future solution for locally advanced BSCs despite the presence of a squamous component in the tumors.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the cases of 4 patients with locally advanced BSC treated effectively with vismodegib have been reported recently. All lesions went into complete remission, which in two cases was maintained for a very long time ( 86 88 ).…”
Section: Basosquamous Carcinomamentioning
confidence: 95%
“…They were often still present at the time of presentation, and spinal metastasis was in the setting of multiorgan involvement, particularly the regional lymph nodes. [33][34][35][36] Conversely, our patient presented to us 10 years after excision of a distant primary on his cheek with a 1-year history of back pain. Spinal metastasis was not accompanied by regional lymph node involvement.…”
Section: Involvement Of Bone By Mbcc: Clinical Presentation and Possi...mentioning
confidence: 99%
“…They were often still present at the time of presentation, and spinal metastasis was in the setting of multiorgan involvement, particularly the regional lymph nodes. 33–36…”
Section: Involvement Of Bone By Mbcc: Clinical Presentation and Possi...mentioning
confidence: 99%